The Scientific Questioning and Experimental Skills of Elementary School Students: The Intervention of Research-Based Learning - Khumraksa, B.; Burachat, P. (Jurnal Pendidikan IPA Indonesia, 2022)
Research-based learning is a learning strategy that encourages the use of scientific inquiry, thereby allowing students to develop an understanding of the scientific process. The aim of this study was to design a research-based, scientific learning activity on the topic of the mass and volume of matter, to be implemented with elementary school students. The study sample consisted of 16 fourth-grade students selected by purposive sampling. This mixed methods study, performed as an embedded design, examined the pre-experimental results of this research-based learning activity on students’ scientific questioning and experimental skills. The science process skills evaluation form was used as a quantitative instrument. The quantitative data were analyzed by simple statistics including mean and standard deviation. Meanwhile, the gathering of qualitative data was accomplished through the taking of field notes. Deductive analysis was employed to highlight the patterns that emerged regarding the students’ science process skills. The findings revealed that this research-based learning design encouraged students’ scientific questioning and experimental skills, with the mean level being at the developing level. This was achieved by giving students the opportunity to engage in challenging, age-appropriate activities with explicit scientific methodology guidance provided by their teachers. Furthermore, it was found that the students were very much satisfied with this research-based learning activity. This suggests that incorporating research-based practices would serve to fulfill the educational aims of the science classroom. The science inquiry-based approach represents an area worthy of increased focus in order to encourage elementary school students to practice science process skills.